Dietary inclusion of ethanolic extracts of jatropha curcas on the performance and carcass characteristics of broiler chickens (2015)
A study was conducted to evaluate the effect of Jatropha curcas leaf extract on the performance and carcass characteristics of broiler chickens. One hundred and fifty day old Arbor Acre broiler chicks were used. They were divided into five treatments and each treatment was replicated five times. Treatment one, (Negative control, no antibiotics), Treatment two (positive control, with antibiotics) while treatments three, four and five had varying inclusion levels of the Jatropha curcas leaf extract (0.25 g/100 kg, 0.50 g/100 kg and 0.75 g/100 kg of feed respectively). The birds were raised for a total number forty two days during which, they were fed ad libitum on a deep litter system of management. Weekly weight gained and feed consumed were recorded. Evisceration of carcass was done after forty two days; each part was weighed and recorded. Performance characteristics indicated no significant (P>0.05) difference in feed consumed and feed conversion ratio, but treatment 4 with 0.50 g/100 kg of Jatropha curcas extract has the best feed conversion ratio, but there were significant (P<0.05) differences in total weight gain.